Transverse Sternal Split: a Safe Mini-invasive Approach for Perventricular Device Closure of Ventricular Septal Defect - Garg,Pankaj (2017)
Abstract Objective: Perventricular device closure of ventricular septal defect through midline sternotomy avoids the cardiopulmonary bypass, however, lacks the cosmetic advantage. Perventricular device closure of ventricular septal defect with transverse split sternotomy was performed to add the cosmetic advantage of mini-invasive technique. Methods: Thirty-six pediatric patients with mean age 7.14±3.24 months and weight 5.00±0.88 kg were operated for perventricular device closure of ventricular septal defect through transverse split sternotomy in 4th intercostal space under transesophageal echocardiography guidance. In case of failure or complication, surgical closure of ventricular septal defect was performed through the same incision with cervical cannulation of common carotid artery and internal jugular vein for commencement of cardiopulmonary bypass. All the patients were postoperatively followed, and then discharged from hospital due to their surgical outcome, morbidity and mortality. Results: Procedure was successful in 35 patients. Two patients developed transient heart block. Surgical closure of ventricular septal defect was required in one patient. Mean duration of ventilation was 11.83±3.63 hours. Mean intensive care unit and hospital stay were 1.88±0.74 days and 6.58±1.38 days, respectively. There was no in-hospital mortality. A patient died one day after hospital discharge due to arrhythmia. No patients developed wound related, vascular or neurological complication. In a mean follow-up period of 23.3±18.45 months, all 35 patients were doing well without residual defect with regression of pulmonary artery hypertension as seen on transthoracic echocardiography. Conclusion: Transverse split sternotomy incision is a safe and effective alternative to a median sternotomy for perventricular device closure of ventricular septal defect with combined advantage of better cosmetic outcomes and avoidance of cardiopulmonary bypass.